Omori‐like decay of postseismic velocities following continental earthquakes - T. Ingleby; T. J. Wright (Geophysical Research Letters)
Abstract Various mechanisms have been proposed to explain the transient, enhanced surface deformation rates following earthquakes. Unfortunately, these different mechanisms can produce very similar surface deformation patterns leading to difficulty in distinguishing between them. Here we return to the observations themselves and compile near‐field postseismic velocity measurements following moderate to large continental earthquakes. We find that these velocities have a remarkably consistent pattern, with velocity inversely proportional to time since the earthquake. This suggests that postseismic velocities show an Omori‐like decay and that postseismic displacements increase logarithmically over time. These observations are inconsistent with simple, linear Maxwell or Burgers body viscoelastic relaxation mechanisms but are consistent with rate‐and‐state frictional afterslip models and power law shear zone models. The results imply that near‐field postseismic surface deformation measurements are primarily the result of fault zone processes and, therefore, that the inference of lower crustal viscosities from near‐field postseismic deformation requires care.